Inflammatory response in CF airway epithelial cells: a comparative study of modulators and wild-type CFTR rescue - Kouadri, Amal; Lyko, Camille; El Hajjar, Carine; Cormenier, Johanna; Kevin Gemy, Kevin; Alfaidy, Nadia; Benharouga, Mohamed (Frontiers in Pharmacology, 2025)
The combination of pharmacological modulators such as lumacaftor, tezacaftor, and elexacaftor restore CFTR activity at the plasma membrane and improve lung function in patients carrying CFTR mutations such as F508del, their effects on inflammation are less clear. This study aimed to investigate whether the inflammatory response in CF airway epithelial cells depends solely on Cl− transport or also on the structural integrity of the CFTR protein. We examined the effects of several CFTR modulators and wild-type CFTR overexpression on CFTR expression, trafficking, Cl− channel activity, and inflammation in human CF bronchial epithelial cells. Our results demonstrate that overexpression of wild-type CFTR fully restores Cl− secretion and normalizes the inflammatory response to levels observed in non-CF cells. In contrast, pharmacological correction of CFTR-F508del leads to partial recovery of Cl− transport and only limited reduction of inflammation. Structural analysis revealed that corrected CFTR-F508del fails to achieve the same conformational stability as wild-type CFTR. These findings suggest that beyond ion transport, the proper folding and structural integrity of CFTR are important for regulating inflammation, potentially through interactions with other cellular proteins involved in inflammatory pathways. This work highlights the need to develop therapeutic strategies that not only restore chloride channel function but also fully correct CFTR misfolding to better control inflammation in CF.